Effects of tea polyphenol and Ca(OH)2 on the intermolecular forces and mechanical, rheological, and microstructural characteristics of duck egg white gel. (September 2019) - Ai, Minmin; Zhou, Quan; Guo, Shanguang; Ling, Ziting; Zhou, Ledan; Fan, Hong; Cao, Yuanyuan; Jiang, Aimin
Abstract: This study investigates the effects of tea polyphenol (TP) and Ca(OH)2 on the physicochemical, mechanical, rheological, and microstructural characteristics of alkali-induced duck egg white (EW) gels. The surface hydrophobicity increases significantly after adding TP, while decreases after adding Ca(OH)2 . Secondary structural analysis indicates that the addition of TP and Ca(OH)2 reduces the β-sheets content and increases the ɑ-helical content. The addition of TP improves the interaction of nonspecific cross-linking but weakens other forces, and the interactions in EW gel are mainly supported by hydrogen bonds and hydrophobic interactions under the influence of Ca(OH)2 . The results of electrophoresis show that crosslinked proteins are formed and the protection provided by TP reduces protein degradation. The addition of a high proportion of TP reduces the storage modulus (G′) of EW gel, decreasing its rigidity and mechanical properties, such as hardness and rupture strength. However, after adding Ca(OH)2, the storage modulus increases gradually and the mechanical strength of EW gel increases, which might be related to the formation of calcium bridges. Scanning electron microscopy indicates that three-dimensional network structures are formed when TP is added, while granular or clustered structures are generated by Ca(OH)2 addition. Correlation analysis shows that the physical properties of EW gel are related to changes in intermolecular forces and the microenvironment, especially pH and nonspecific cross-linking. These results suggest that the addition of TP and Ca(OH)2 affects the physicochemical properties of EW gel differently, which were mainly attributed to the effects of molecular interaction and micro-environment. Graphical abstract: Image 1075 Highlights: TP weakened gel strength while Ca(OH)2 enhanced mechanical properties. Addition of Ca(OH)2 increased hydrogen bonds and hydrophobic interaction content. TP and Ca(OH)2 reduced β-sheet content while increased ɑ-helical. The using of Ca(OH)2 limited the effects of TP on egg white physical properties.